Vitrification and increase of basicity in between ice Ih crystals in rapidly frozen dilute NaCl aqueous solutions - Imrichová, Kamila; Veselý, Lukáš; Gasser, Tobias M; Loerting, Thomas; Neděla, Vilém; Heger, Dominik (The Journal of chemical physics, 2019)
The freezing of ionic aqueous solutions is common in both nature and human-conducted cryopreservation. The cooling rate and the dimensions constraining the solution are known to fundamentally influence the physicochemical characteristics of the sample, including the extent of vitrification, morphology, and distribution of ions. The presence of some salts in an aqueous solution often suppresses the ice crystallization, allowing bulk vitrification during relatively slow cooling. Such a process, however, does not occur in NaCl solutions, previously observed to vitrify only under hyperquenching and/or in sub-micrometric confinements. This work demonstrates that, at freezing rates of ≥100 K min-1, crystallized ice Ih expels the freeze-concentrated solution onto the surfaces of the crystals, forming lamellae and veins to produce glass, besides eutectic crystallization. The vitrification covers (6.8% ± 0.6%) and (17.9% ± 1.5%) of the total eutectic content in 0.06M and 3.4 mM solutions, respectively. The vitrified solution shows a glass-to-liquid transition succeeded by cold crystallization of NaCl · 2H2O during heating via differential scanning calorimetry. We establish that ice crystallization is accompanied by increased basicity in freeze-concentrated solutions, reflecting preferential incorporation of chloride anions over sodium cations into the ice. After the sample is heated above the glass transition temperature, the acidity gradually returns towards the original value. The morphology of the samples is visualized with an environmental scanning electron microscope. Generally, the method of vitrifying the freeze-concentrated solution in between the ice Ih crystals via fast cooling can be considered a facile route towards information on vitrified solutions.